2015
DOI: 10.1016/j.ultsonch.2014.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Anti-metastatic and pro-apoptotic effects elicited by combination photodynamic therapy with sonodynamic therapy on breast cancer both in vitro and in vivo

Abstract: Sono-Photodynamic therapy (SPDT), a new modality for cancer treatment, is aimed at enhancing anticancer effects by the combination of sonodynamic therapy (SDT) and photodynamic therapy (PDT). In this study, we investigated the antitumor effect and possible mechanisms of Chlorin e6 (Ce6) mediated SPDT (Ce6-SPDT) on breast cancer both in vitro and in vivo. MTT assay revealed that the combined therapy markedly enhanced cell viability loss of breast cancer cell lines (MDA-MB-231, MCF-7 and 4T1) compared with SDT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 30 publications
(35 reference statements)
0
50
0
5
Order By: Relevance
“…8 SDT induces the generation of reactive oxygen species (ROS) and apoptosis in tumor cells, and has been shown to greatly improve the outcome of cancer patient by promoting tumor shrinkage while reducing metastases of tumor cells. 9, 10, 11, 12, 13 We previously revealed that SDT could effectively induce apoptosis of macrophage and macrophage foam cell via mitochondrial-caspase dependent pathway 14, 15 and rapidly stabilize atherosclerotic plaques. 16 Meanwhile, SDT possesses high repeatability owing to its relative security and accessibility.…”
mentioning
confidence: 99%
“…8 SDT induces the generation of reactive oxygen species (ROS) and apoptosis in tumor cells, and has been shown to greatly improve the outcome of cancer patient by promoting tumor shrinkage while reducing metastases of tumor cells. 9, 10, 11, 12, 13 We previously revealed that SDT could effectively induce apoptosis of macrophage and macrophage foam cell via mitochondrial-caspase dependent pathway 14, 15 and rapidly stabilize atherosclerotic plaques. 16 Meanwhile, SDT possesses high repeatability owing to its relative security and accessibility.…”
mentioning
confidence: 99%
“…11,12 Besides, it is currently believed that the combination of PDT and sonodynamic therapy (SDT) may decrease the sensitizer dosage and ultrasound/ light energy, which can further reduce the side effects, while enhancing the curative effect dramatically. [13][14][15][16][17] Thus, PDT combined with SDT (PSDT) is considered for the lesion of deep site in the present study. The underlying mechanisms of PDT and SDT are quite different, and the mechanisms of PSDT are very complicated.…”
mentioning
confidence: 99%
“…The effect of PDT and SDT combination therapy is coincident with previous reports, except that in our study, the process was activated in sequence by light and ultrasound. 14,16 The cellular uptake and intracellular distribution of sensitizers is potentially important for PDT and SDT. So, we determined the uptake ability of MH7A cells for free ICG and OI-NPs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The plane transducer was placed in a water tank filled with degassed water and the temperature was kept at 37°C during ultrasonic exposure. The ultrasound parameters were measured as described in our previous studies [17].…”
Section: Sonodynamic Treatmentmentioning
confidence: 99%